Enhancing Photonic Spin Hall Effect in the Surface Plasmon Resonance Structure Covered by the Graphene–MoS2 Heterostructure - Qingkai Wang; Xing Jiang; Xi Wang; Xiaoyu Dai; Yuanjiang Xiang (IEEE Photonics Journal, 2017)
Due to the weak spin–orbit interaction, the photonic spin Hall effect (SHE) is generally very weak, which is disadvantageous for potential applications of nanophotonic devices. Surface plasmon resonance (SPR) has been proposed to enhance the photonic SHE. In this paper, by covering the heterostructure material composed of graphene and molybdenum sulfide (MoS2) on the SPR structure, it is demonstrated that the two-dimensional (2-D) material heterostructure can effectively enhance the photonic SHE. The transverse shift of light beam in the heterostructure is larger than those in SPR structure due to the larger refractive index gradient in the heterostructure. The maximum transverse shift can be up to 27.5 μm under the optimized parameters, which is much larger than the previously reported values. This interesting phenomenon is attributed to the larger light absorption and hence the refractive index variation gradient of graphene/MoS2 heterostructure. These findings provide us with a new way to modulate the photonic SHE, and also establish foundation for developing nanophotonic devices based on 2-D nanomaterials heterostructure.